Experimental study on the effect of Ivermectin on cattle dung faunas in Eastern Ethiopia - Shiret Belete; Hunde Adugna; Tsedalu Yirsa (PLoS ONE, 2025)
An experimental investigation was conducted from December 2023 to June 2024 at the beef farm of Haramaya University. The bulls were divided into two groups: one group received ivermectin treatment, while the other acted as a control. The SUMIVER brand of ivermectin was administered subcutaneously at 1 ml per 50 kg of body weight. Dung samples from both groups were collected and prepared for analysis at five-day intervals during the eighth sampling period. The results were measured, documented, and analyzed both qualitatively and quantitatively. All data were entered and analyzed using an independent t-test with the STATA-14 software. In the qualitative assessment, no dipteran larvae or pupae were detected in the dung samples, except during the eighth round. However, various species of invertebrates were attracted to the freshly managed dung, resulting in a higher visitation rate in the control group compared to the experimental group. In the initial weeks of the study, the presence of ivermectin residues affected the dung beetle population. Conversely, the treated dung showed a significant infestation of termites. After several weeks, both groups of dung pats were invaded by ants, with the control group experiencing infestation first. These findings suggest that ivermectin residues released into the environment through cattle dung can influence negatively plant germination, dung fauna, and soil fertility. Therefore, it is crucial for veterinarians to be knowledgeable about the environmental side effects of ivermectin and to offer guidance to livestock owners.